Seed Vigor as Influenced by Rhizospheric Bacterial Isolates in Soybean (Glycine max L. Merril) - BIRENDRA PRASAD; AMRENDRA KUMAR; AJAY VEER SINGH; AMARJEET KUMAR; RAJENDRA PRASAD (Seed Research, 2026)
Plant growth promoting rhizobacteria (PGPR) have been reported to influence the seed germination and subsequent seedling growth by an array of mechanisms, the specific traits by which PGPR promote growth and yield were limited to the expression of one or more of the traits expressed at a given environment of plant-microbe interaction. The present investigation was carried out to study the influence of bacterial isolates on seed germination and seedling vigour in soybean, under control condition. The experimental material consists of two variety of Soybean viz., PRS-1 and PS-1092 which were inoculated with 10 different isolates of PGPR namely RGB-1, RMV-1, RMV-2, RMV-3, RMV-4, RPB-1, RPB-3, RPB-4, RPB-5 and RPV-4, obtained from the chickpea, mustard and pea rhizosphere and Pf-102 was used as standard check along with un-inoculated control. Under laboratory conditions, out of eleven bacterial isolates, RMV- 4 exhibited greater number of germination with respect to standard germination and first count for both the cultivars (PRS-1 and PS-1092). However, root and seedling length, fresh and dry weight as well as vigour index were found to be better for RPB-1, while RMV-2 produced longer shoot.